The Impact of Diabetic Conditions and AGE/RAGE Signaling on Cardiac Fibroblast Migration - Burr, Stephanie D.; Harmon, Mallory B.; Jr., James A. Stewart (Frontiers in Cell and Developmental Biology, 2020)
Diabetic individuals have an increased risk for developing cardiovascular disease due to stiffening of the left ventricle, which is thought to occur, in part, by increased AGE/RAGE signaling inducing fibroblast differentiation. Advanced glycated end products (AGEs) accumulate within the body over time, and under hyperglycemic conditions, the formation and accumulation of AGEs is accelerated. AGEs exert their effect by binding to their receptor (RAGE) and can induce myofibroblast differentiation, leading to increased cell migration. Previous studies have focused on fibroblast migration during wound healing, in which diabetics have impaired fibroblast migration compared to healthy individuals. However, the impact of diabetic conditions as well as AGE/RAGE signaling has not been extensively studied in cardiac fibroblasts. Therefore, the goal of this study was to determine how the AGE/RAGE signaling pathway impacts cell migration in non-diabetic and diabetic cardiac fibroblasts. Cardiac fibroblasts were isolated from non-diabetic and diabetic mice with and without functional RAGE and used to perform a migration assay. Cardiac fibroblasts were plated on plastic, non-diabetic, or diabetic collagen, and when confluency was reached, a line of migration was generated by scratching the plate and followed by treatment with pharmacological agents that modify AGE/RAGE signaling. Modification of the AGE/RAGE signaling cascade was done with ERK1/2 and PKC-ζ inhibitors as well as treatment with exogenous AGEs. Diabetic fibroblasts displayed an increase in migration compared to non-diabetic fibroblasts whereas inhibiting the AGE/RAGE signaling pathway resulted in a significant increase in migration. The results indicate that the AGE/RAGE signaling cascade causes a decrease in cardiac fibroblast migration and altering the pathway will produce alterations in cardiac fibroblast migration.